El amor en línea: Procesos psicológicos y evolución de las relaciones online y offline en adultos jóvenes de México - Vizzuetth Herrera, Aleyda (2024)
The purpose of this research was to analyze the characteristics, motivations and perceptions of people in online relationships, as well as the differences in the evolution of these compared to traditional offline relationships in young adults from different states of Mexico, users and non-users of online dating apps through mixed-type exploratory sequential research that combines qualitative and quantitative phases. In the virtual world, the psychological aspects of the love process such as passion, commitment, intimacy, motivation, and the evolution of relationships occur in a personal and symbolic imaginary in the absence of physical contact. The first gathered information from 545 people who are users and non-users of dating apps. The second phase was carried out throughout six online in-depth interviews to better understand findings in the first exploratory stage. Findings support more similarities than differences in the establishment and evolution of online and in-person relations. For example, there is a fear of lack of honesty and eventual commitment and in general all participants initially expect to consolidate eventually their relationship. Online dating is perceived as adventuresome, and it is motivated to increase the opportunities to meet someone outside the real social context. In conclusion, virtual tools can help to start a romantic relationship, however, that doesn´t guarantee a successful relationship. The findings don´t support the notion that love online is a psychologically different than offline relationships, rather this is seen as a first exploratory stage in a romantic relationship.